Dengue antibodies in blood donors - Ribas-Silva,Rejane Cristina (2012)
BACKGROUND: Dengue is an urban arbovirus whose etiologic agent is a virus of the genus Flavorius with four distinct antigen serotypes (DENV-1, DENV-2, DENV-3 and DENV-4) that is transmitted to humans through the bite of the mosquito Aedes aegypti. The Campo Mourão region in Brazil is endemic for dengue fever. OBTECTIVE: The aim of this study was to evaluate the presence of IgG and IgM antibodies specific to the four serotypes of dengue in donors of the blood donor service in the city of Campo Mourão. METHODS: Epidemiological records were evaluated and 4 mL of peripheral blood from 213 blood donors were collected in tubes without anticoagulant. Serum was then obtained and immunochromatographic tests were undertaken (Imuno-Rápido Dengue IgM/IgG TM). Individuals involved in the study answered a social and epidemiological questionnaire on data which included age, gender and diagnosis of dengue. RESULTS: Only three (1.4%) of the 213 blood tests were positive for IgG anti-dengue antibodies. No donors with IgM antibody, which identifies acute infection, were identified. CONCLUSIONS: The results of the current analysis show that the introduction of quantitative or molecular serological methods to determine the presence of anti-dengue antibodies or the detection of the dengue virus in blood donors in endemic regions should be established so that the quality of blood transfusions is guaranteed.